“You can’t go to the army and expect to be a Vice-Chancellor”: They must become good scholars - Buccus, I. (South African Journal of Higher Education, 2022)
This article is a study of a university vice chancellor (VC) and specifically the leadership qualities that articulate success. There is broad agreement across the higher education sector that good leadership is central to the performance of university vice chancellors (Cloete, Maassen, and Bailey 2015; Macfarlane 2012; Jansen 2017; Scott et al. 2010). University vice-chancellor’s performance are measured against at range of issues and include determining the institution’s strategic goals, academic standing and transformation agenda (Leibowitz 2012). To run a university there is need for university vice-chancellors to articulate particular skills, values and qualities that will enable them to achieve success in these wide-ranging and competing goals and agendas. In South Africa however with few exceptions (Swartz et al. 2019; Jansen 2017), fundamental questions remain about what these values and qualities are and they arise in university vice-chancellors own account of leadership. Although vice-chancellors occupy an eminent position in the country especially in the context of transforming higher education in the country (Cloete 2014), specific attention to the values and qualities that vice-chancellors articulate as vital for leadership has been understudied. This article is interested in the question: how do vice-chancellors shape leadership qualities are how do these arise? This question is explored empirically, through narrative enquiry by focusing on one vice-chancellor’s account of leadership qualities. Through a close-focus examination of the nuances associated with a university vice chancellor’s conceptualisation of leadership, this article provides insights into what qualities are relevant for effective leadership. As noted by Dewan and Myatt (2008) the successful performance of a leader is based on the question of which qualities are relevant for effective leadership. There remains a marginal consideration of university vice-chancellor’s perspectives on the issues of effective leadership and how they arise especially in the context of South Africa’s turbulent higher education environment.